2013
DOI: 10.1055/s-0033-1361145
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Smoking and Alcohol during Pregnancy on Outcome of VLBW Infants

Abstract: Smoking during pregnancy results in a high rate of growth restricted VLBW infants. Prenatal exposition to nicotine seems to increase postnatal complications such as BPD und ROP.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
18
0
3

Year Published

2015
2015
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(21 citation statements)
references
References 9 publications
0
18
0
3
Order By: Relevance
“…This is consistent with the findings of Zarnowiecki et al where parents of low SES were less likely to model healthy eating behaviours (Zarnowiecki et al ). Moreover, the risk factor of birth weight suggests that this unhealthy environment was in place prenatally, given evidence that low birth weight is associated with several unhealthy behaviours such as smoking and alcohol consumption (Spiegler et al ) and high birthweight is associated with gestational diabetes (Heslehurst et al ), excessive gestational weight gain (Surkan et al ) and decreases in maternal smoking (Hadfield et al ). An unhealthy early childhood home environment may explain why regular child‐care attendance was found to protect infants from COWOB.…”
Section: Discussionmentioning
confidence: 99%
“…This is consistent with the findings of Zarnowiecki et al where parents of low SES were less likely to model healthy eating behaviours (Zarnowiecki et al ). Moreover, the risk factor of birth weight suggests that this unhealthy environment was in place prenatally, given evidence that low birth weight is associated with several unhealthy behaviours such as smoking and alcohol consumption (Spiegler et al ) and high birthweight is associated with gestational diabetes (Heslehurst et al ), excessive gestational weight gain (Surkan et al ) and decreases in maternal smoking (Hadfield et al ). An unhealthy early childhood home environment may explain why regular child‐care attendance was found to protect infants from COWOB.…”
Section: Discussionmentioning
confidence: 99%
“…Many researchers have investigated if there is an association between maternal smoking and BPD. Population-based cohort studies from Italy, Germany, and Canada have shown that preterm infants born to mothers who smoke during pregnancy have an increased risk of developing BPD 5052 . In preclinical studies, exposure of pregnant rodents to cigarette smoke or nicotine has also shown to cause a lung phenotype identical to that seen in human infants with BPD 53,54 .…”
Section: Pathogenesismentioning
confidence: 99%
“…The confounder must be associated with the predictor of interest (ie, smoking during pregnancy is more common among coffee or caffeine drink consumers) (9) and also be a cause of the outcome (smoking can independently cause fetal growth restriction). (10)…”
Section: Bias and Confoundingmentioning
confidence: 99%